Subtrochlear sclerosis evaluation for medial coronoid disease detection and dynamic distal ulnar ostectomy for reduction of disease progression in Labrador retriever puppies - Irvine-Smith, Greg (University of Pretoria, 2024)
Dissertation (MMedVet (Surgery) (Small Animals))--University of Pretoria, 2023.